Peanut yield as affected by liming and drying method - Fernandes, Elena Mercedes; Rosolem, Ciro Antonio (Pesquisa Agropecuaria Brasileira, 1999)
Peanut (Arachis hypogea L.), cv. Botutatu was grown in a Dark Red Latosol (Haplortox, sandy loam) in São Manuel, São Paulo, to study the effects of liming and drying method on grain yields. Treatments consisted of lime rates (0 and 2.05 Mg ha-1) and the drying methods: shadow, field and two combinations of field + oven. Manganese toxicity desapeared in limed plots, providing a better nodulation and N nutrition, which in turn, led to a higher plant branching, a higher number of fruits per plant and higher yields. Yield losses were lower in limed plots. The plots dried in the shadow and in the combined field + oven method yielded more than those field dried because they allowed a better fruit maturation and lower yield losses.